PENGARUH EKSTRAK ETANOL KULIT BUAH NAGA MERAH (Hylocereus Polyrhizus) TERHADAP KOGNITIF MENCIT GALUR SWISS WEBSTER DENGAN INDUKSI ALKOHOL - Larasati, Fidya (Jurnal Mahasiswa Kesehatan, 2021)
The red dragon fruit skin plant (Hylocereus polyrhizus) has high antioxidant activity so it has the potential to treat several diseases. The purpose of this study was to determine the effect of ethanol extract of red dragon fruit skin on cognitive and memory of mice and to determine the best dose in increasing memory of mice. Red dragon fruit skin simplicia is obtained from Mojokerto Regency and extracted using 96% alcohol. The test animals in this study were divided into 5 treatment groups, that is negative control 0.5% Na CMC, positive control ginko biloba, and variations in the dose of red dragon fruit skin (Hylocereus polyrhizus) ethanol extract of 100 mg / Kg BW for mice, 200 mg. Mice / Kg BW and 400 mg / Kg BW of mice were given orally and the data on the memory score of mice during the trial, after 10% alcohol induction, and after treatment for approximately 30 days were obtained. The method of this research is radial arm maze, a technique for studying serial learning sequences and calculating memory scores in test animals.The results of statistical analysis showed that the third dose of 400 mg / Kg BW for mice was not significantly different from the positive control for ginko biloba 0.312 mg / 20 gram BW for mice so that it can be concluded that the best dose in increasing memory of mice is dose III 400 mg / Kg BW of mice.Keywords: hylocereus polyrhizus, red dragon fruit skin, memory score, radial arm maze